2000
DOI: 10.1074/jbc.275.8.5904
|View full text |Cite
|
Sign up to set email alerts
|

Association of Human Origin Recognition Complex 1 with Chromatin DNA and Nuclease-resistant Nuclear Structures

Abstract: An origin recognition complex (ORC) consisting of six polypeptides has been identified as a DNA replication origin-binding factor in Saccharomyces cerevisiae. Homologues of ORC subunits have been discovered among eukaryotes, and we have prepared monoclonal antibodies against a human homologue of ORC1 (hORC1) to study its localization in human cells. It was thus found to associate with nuclei throughout the cell cycle and to be resistant to nonionic detergent treatment, in contrast to MCM proteins, which are ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
2
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 51 publications
5
55
2
1
Order By: Relevance
“…Studies on Mcm10 modification revealed that phosphatase converted the slower migrating form in the metaphase extract to the faster migrating form in S phase extract. It seems that Mcm10 is phosphorylated by protein kinase(s) in G 2 /M phase, similar to Orc1 (40,41), Orc2 (42), Mcm2, and Mcm4 (21,43). One possible kinase candidate is cdc2/cyclin B1, since the mobility shift of Mcm10 to a slower migrating form occurred in conjunction with an increase in cyclin B1.…”
Section: Fig 3 Proteasome Inhibitors Stabilize Mcm10mentioning
confidence: 99%
“…Studies on Mcm10 modification revealed that phosphatase converted the slower migrating form in the metaphase extract to the faster migrating form in S phase extract. It seems that Mcm10 is phosphorylated by protein kinase(s) in G 2 /M phase, similar to Orc1 (40,41), Orc2 (42), Mcm2, and Mcm4 (21,43). One possible kinase candidate is cdc2/cyclin B1, since the mobility shift of Mcm10 to a slower migrating form occurred in conjunction with an increase in cyclin B1.…”
Section: Fig 3 Proteasome Inhibitors Stabilize Mcm10mentioning
confidence: 99%
“…Briefly, cells were labeled with BrdUrd for 10 min and detected using a monoclonal antibody against BrdUrd and a fluorescein-conjugated second antibody, as specified by the manufacturer. Cells were also stained with 4,6-diamidino-2-phenylindole (DAPI) as described previously (25). The fluorescent signals were visualized with a Leica DMRBE and captured with Photometrics PXL.…”
Section: Methodsmentioning
confidence: 99%
“…Hydroxyurea (HU) was included at 2.5 mM. Synchronized growth was monitored by flow cytometry (BD Biosciences) of propidium iodide-stained cells (25), by immunoblot analysis of cyclin E and cyclin A levels, and by 5-bromo-2Ј-deoxy-uridine (BrdUrd) incorporation. Incorporated BrdUrd was detected using the 5-Bromo-2Ј-deoxyuridine Labeling and Detection Kit I (Roche Applied Science, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations